INTEGRASI DEEP LEARNING DAN PEMBELAJARAN SOSIAL EMOSIONAL DALAM PENINGKATAN KOMPETENSI GURU SMK MUHAMMADIYAH LONG IKIS - Nur Fatimah Azzahra; Anisa Rahmi Fakhriyana; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the integration of deep learning and social-emotional learning (SEL) in enhancing teacher competence at SMK Muhammadiyah Long Ikis, an Islamic vocational school that emphasizes academic, moral, and emotional balance. The research was motivated by the limited systemic implementation of deep learning and SEL, as well as challenges teachers face in digital literacy, emotional regulation, and designing contextual learning. Using a descriptive qualitative approach with a case study design, data were collected through interviews, classroom observations, and document analysis involving school leaders and teachers from several vocational programs. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that although formal guidelines for integrating deep learning and SEL are absent, teachers have initiated reflective and contextual learning practices. Deep learning was evident in Informatics classes, where students engaged in problem-based tasks using keyboard shortcuts within real-world IT scenarios. SEL practices appeared in teachers’ empathetic communication and emotional check-ins, although not systematically embedded in lesson planning. The integration of both approaches contributed to improvements in pedagogical, professional, social, and personal competencies of teachers, particularly in reflective practice, communication skills, emotional regulation, and classroom interaction. The study concludes that effective integration requires institutional support, structured training, and operational guidelines to ensure sustainability. This research offers a culturally relevant model for integrating deep learning and SEL in vocational education settings. Keywords: deep learning, social emotional learning, teacher competences